Performance analysis of antenna selection scheme in dual-hop NOMA HD and FD energy harvesting relay networks - Demirkol, Busra; Aldababsa, Mahmoud; Toka, Mesut; Kucur, Oğuz (Elsevier Gmbh, 2022)
In this paper, the outage probability (OP) performance of antenna selection schemes is investigated in downlink non-orthogonal multiple access based energy harvesting amplify-and-forward relay network. In this network, base station with multiple antennas simultaneously communicates with multiple-antenna users via the relay, which is equipped with single transmit and multiple receive antennas and operates in half-duplex (HD) or fullduplex (FD) mode. The joint transmit-receive antenna selection and receive antenna selection schemes are employed in the first and second hops, respectively. For the proposed system, the closed-form expressions for the exact OP are derived jointly for HD and FD modes over Nakagami-m fading. Then, the corresponding asymptotic OP expressions are obtained. Finally, accuracy of our analyses is verified by simulations.
Keywords: Antenna selection; Energy harvesting; Full-duplex; Half-duplex; Non-orthogonal multiple access